2015
DOI: 10.1111/apt.13319
|View full text |Cite
|
Sign up to set email alerts
|

Factors governing long‐term adherence to a gluten‐free diet in adult patients with coeliac disease

Abstract: SUMMARY BackgroundA strict gluten-free diet is the cornerstone of treatment for coeliac disease. Studies of gluten-free diet adherence have rarely used validated instruments. There is a paucity of data on long-term adherence to the gluten-free diet in the adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
80
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 27 publications
8
80
1
2
Order By: Relevance
“…The gluten-free diet may be difficult to pursue in some countries that have limited access to gluten-free products, or in settings where limited or minimal financial support is available[15], especially from government or other health care providers. Gluten-free diets are generally costly and perceived cost remains a barrier to adherence[16]. In some countries, governments may provide a stipend to alleviate costs or, alternatively, consider the costs of a gluten-free diet as an annual tax credit to the well-documented patient with biopsy-defined celiac disease[17].…”
Section: Gluten-free Diet Treatmentmentioning
confidence: 99%
“…The gluten-free diet may be difficult to pursue in some countries that have limited access to gluten-free products, or in settings where limited or minimal financial support is available[15], especially from government or other health care providers. Gluten-free diets are generally costly and perceived cost remains a barrier to adherence[16]. In some countries, governments may provide a stipend to alleviate costs or, alternatively, consider the costs of a gluten-free diet as an annual tax credit to the well-documented patient with biopsy-defined celiac disease[17].…”
Section: Gluten-free Diet Treatmentmentioning
confidence: 99%
“…The authors’ declarations of personal and financial interests are unchanged from those in the original article …”
Section: Acknowledgementmentioning
confidence: 99%
“…We appreciate the interest of Kurien et al . in our study looking at factors governing long‐term adherence to a gluten‐free diet (GFD) . Our database unfortunately did not record the frequency of clinical follow‐up during the period on a GFD.…”
mentioning
confidence: 99%
“…As an example, consuming a GFD does not make one more female and hence might not contribute toward weight loss or to the lack of other metabolic or cardiac risk factors. As following a GFD is associated with higher educational attainment and income, and improved self-awareness [7], one might have predicted, a priori, that cardiovascular risk profiles would be superior to those of the average population eating gluten. Despite using a large database like NHANES, the study only identified 155 nonceliac GFD followers.…”
mentioning
confidence: 99%